HUBUNGAN ORIENTASI KEWIRAUSAHAAN, ADOPSI E-COMMERCE DAN INOVASI PRODUK DENGAN KINERJA UMKM DI KABUPATEN SUMBAWA - Marisa Sutanty; Subhan Purwadinata; Septiriana Aluh Indah (Samalewa: Jurnal Riset & Kajian Manajemen, 2023)
This study aims to know the effect of entrepreneurial orientation, e-commerce adoption and product innovation on the performance of micro, small and medium enterprise (MSME) of woven fabrics in Samri Hamlet, Poto Village, Moyo Hilir Sub district, Sumbawa District. The type of this study was associative study. The type of data used is quantitative data obtained directly from primary sources. The population in this study were all weaving craftsmen in Samri Hamlet, Poto Village, totaling 64 people. Determination of the sample was carried out using a saturated sampling technique so that the number of samples in this study were 64 respondents. The data used were collected through questionnaires and analyzed using multiple linear regression analysis techniques, individual hypothesis testing (t test), simultaneous hypothesis testing (F test), and determinant coefficient test (R2). The results showed that entrepreneurial orientation, e-commerce adoption and product innovation had a positive and significant effect on the performance of woven cloth MSMEs in Samri Hamlet, Poto Village, Moyo Hilir Sub District, Sumbawa District, both partially and simultaneously. The degree of influence of entrepreneurial orientation, e-commerce adoption and product innovation on the performance of woven fabric MSMEs in Samri Hamlet, Poto Village, Moyo Hilir Sub District, Sumbawa District is 6.68%, while the remaining 33.2% is influenced by other variables outside this research model, such as capital, market orientation, and orientation of entrepreneurship.